Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan Pelanggan di Warkop Agam Jalan Tanjung Selamat - Izzah, Edsan Faris; Lubis, Adelina (Mahesa Research Center, 2025)
This study aims to analyze the influence of price and product quality on customer satisfaction at Warkop Agam Jalan Tanjung Selamat. The research method used is associative research with a quantitative approach. The population in this study is Warkop Agam customers over the past month, with a total of 701 customers. The sample was determined using the Slovin formula, so that 87 respondents were obtained. Data analysis was carried out by descriptive methods and multiple linear regression with a significance level of 0.05. The results showed that (1) product quality had a positive and significant influence on customer satisfaction, with a significance value of 0.000 0.05 and t-count 6.601 t-table 1.988, (2) price also had a positive and significant effect on customer satisfaction, with a significance value of 0.000 0.05 and t-count 5.032 t-table 1.988, and (3) product quality and price simultaneously had a significant effect on customer satisfaction. Regression analysis shows that product quality and price together explain 84.1% variability in customer satisfaction, as indicated by an Adjusted R Square value of 0.841. The results of the study show that improving product quality and price adjustment can increase customer satisfaction. Warkop Agam managers are advised to maintain quality, increase menu variety, and set competitive prices to maintain customer loyalty in the midst of business competition.